SISTEM INFORMASI KEUANGAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDes) PADA DESA SIDOREJO MENGGUNAKAN METODE ACCRUAL BASIC - Siti Romadonah (Jurnal Ilmiah Sistem Informasi, 2023)
This research aims to determine the Village Revenue and Expenditure Budget which includes: planning, implementation, administration, reporting, accountability for managing the finances of Sidorejo village. The research method used is Accrual Basic by comparing village financial management in accordance with Regent Regulation (Perbup) Number 8 of 2015 concerning Village Financial and Asset Management. With existing financial data collection techniques and direct observation of research objects. Determination of observation areas is carried out by considering the size of village fund receipts or village fund allocations. The results of this research show that based on Regent's Regulations (Perbup) Number 8 of 2015 concerning Village Financial Management, in general, Village Financial Management has achieved accountability. Apart from that, there is still a need for intensive village assistance from the regional government in helping villages to realize accountability in Village Financial Management.